(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
Based on the analysis of the "AL1 nas Comunidades" section of TV Gazeta de Alagoas, this work addresses the concept of Information Regime. The aforementioned table publicizes the problems of local communities and demands actions from public authorities, in the city of Maceió, state of Alagoas. The general objective of this work is to examine the information regime of community journalism, verifying its elements and effectiveness. The methodology adopted combines a qualitative and quantitative approach. The research involves analysis of 838 reports, which were aired between 2019 and 2023, and which are available on TV Globo’s Globo Play website. Data analysis identifies positive and negative points in the situation, proposing improvements. The inferences are based on the adopted theoretical framework, contributing to the understanding of the information process in journalistic production in the context of communities.